Quantification of Metformin in Human Urine by Using Ion-pair HPLC Method - Eva Troja; Leonard Deda (Medicine and Medical Research: New Perspectives Vol. 2, 2024)
The aim of this study was to develop and validate a selective and sensitive ion-pairing HPLC–UV method for the determination of metformin in human urine using a conventional reversed-phase column. Urine provides a non-invasive sample collection method, and the determination of drug levels in urine is comparatively less complex than in plasma and other body fluids. The bioanalytical method was carried out using an RP-C18 column (250×4.0 mm; 5 \(μ\)m). A mobile phase consisting of acetonitrile and 10 mM sodium phosphate buffer (pH=6.0, 30:70 v/v) and sodium dodecyl sulfate (0.3%) was pumped at an isocratic flow rate of 1.00 mL/minute and quantification was achieved at 236 nm using a UV/VIS DAD. The applicability of the method was confirmed in a study of urinary excretion of metformin by healthy volunteers after oral administration of commercially available tablets. The calibration curves were linear (r2 >0.999) in the concentration ranges of 62.5–2000 \(μ\)g/mL for metformin in urine. LOD and LOQ were found to be 12 \(μ\)g/mL and 35 \(μ\)g/mL, respectively. The method was found to be rapid, precise, and accurate for quantification of metformin in human urine. The study illustrates the characteristics of drug excretion at a single dose of metformin in healthy subjects. Drug excretion is in the trend of increase and accumulation, but the discharge rate is not constant, the accumulative urine drug method can indirectly reflect the metabolic process of the drug in the body. This method was successfully applied to a pharmacokinetic study of humans through oral administration.